2022
DOI: 10.1186/s13568-022-01481-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of protein profile in metacyclic and amastigote-like stages of Leishmania tropica: a proteomic approach

Abstract: Leishmaniasis is a tropical disease that leads to various clinical phenotypes. This study aimed to investigate protein expression changes in metacyclic and amastigote-like stages of L. tropica isolated from Iranian cutaneous leishmaniasis patients. Isolated samples were cultured and species type identified using PCR–RFLP technique. The promastigotes were grown in RPMI1640 media and differentiated to metacyclic and amastigote-like forms, followed by the extracted proteins of both successive stages carried out f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The authors, through genomic, transcriptomic, and proteomic analyses, demonstrated that some biological processes such as “ribosome biogenesis”, “ribosome assembly” and “rRNA processing” have an important role in fitness gain by forming “fitness-adapted ribosomes”, which can change the translation specificity or efficiency and allows the environment adaptation of Leishmania to changing conditions [ 111 ]. Likewise, a quantitative proteomic analysis also revealed that some ribosomal proteins are differentially expressed in the life cycle of L. tropica , L. major , and L. donovani, being up or down-regulated in different stages of the differentiation process in all species, indicating that ribosomal proteins are involved in the most important pathways of the metacyclogenesis mechanisms [ 112 , 113 , 114 ] ( Figure 5 and Figure 6 A–F).…”
Section: Ribosome Specialization In Trypanosomatidsmentioning
confidence: 95%
See 2 more Smart Citations
“…The authors, through genomic, transcriptomic, and proteomic analyses, demonstrated that some biological processes such as “ribosome biogenesis”, “ribosome assembly” and “rRNA processing” have an important role in fitness gain by forming “fitness-adapted ribosomes”, which can change the translation specificity or efficiency and allows the environment adaptation of Leishmania to changing conditions [ 111 ]. Likewise, a quantitative proteomic analysis also revealed that some ribosomal proteins are differentially expressed in the life cycle of L. tropica , L. major , and L. donovani, being up or down-regulated in different stages of the differentiation process in all species, indicating that ribosomal proteins are involved in the most important pathways of the metacyclogenesis mechanisms [ 112 , 113 , 114 ] ( Figure 5 and Figure 6 A–F).…”
Section: Ribosome Specialization In Trypanosomatidsmentioning
confidence: 95%
“…Several proteomic analyses have shown that ribosomal proteins as well as proteins related to ribosome biogenesis are some of the most up or downregulated proteins in the transition stage [ 108 , 112 , 113 , 141 ]. However, it is necessary to highlight that some ribosomal proteins exhibit extraribosomal functions in other organisms, such as acting as DNA endonucleases (RPS3/uS3) [ 142 , 143 ], helping in antiviral responses (RPL10/uL16, RPL13A/uL13) [ 144 , 145 ], and even being part of the small nucleolar ribonucleoproteins (snoRNP) (RPL7/uL30) [ 146 ]; some act in autoregulation of RP synthesis and as sentinels in ribosome biosynthesis, among other functions [ 147 , 148 , 149 , 150 ].…”
Section: Role Of Ribosome Specialization In Parasitismmentioning
confidence: 99%
See 1 more Smart Citation